Climate change, disease range shifts, and the future of the Africa lion. Issue 5 (4th May 2018) - Carter, Neil H.; Bouley, Paola; Moore, Sean; Poulos, Michael; Bouyer, Jérémy; Pimm, Stuart L.
Abstract : Article impact statement : Understanding causes and consequences of disease range shifts can help mitigate negative effects of such shifts on lions and other wildlife.